Diffraction Study on the Thermal Stability of Ti3SiC2/TiC/TiSi2 Composites in Vacuum - Pang, Wei Kong; Low, It-Meng (Jim); O'Connor, Brian; Studer, A.; Peterson, V.; Palmquist, J. (American Institute of Physics, 2010)
Titanium silicon carbide (Ti3SiC2) possesses a unique combination of properties of both metals and ceramics, for it is thermally shock resistant, thermally and electrically conductive, damage tolerant, lightweight, highly oxidation resistant, elastically stiff, and mechanically machinable. In this paper, the effect of high vacuum annealing on the phase stability and phase transitions of Ti3SiC2/TiC/TiSi2 composites at up to 1550° C was studied using in-situ neutron diffraction. The role of TiC and TiSi2 on the thermal stability of Ti3SiC2 during vacuum annealing is discussed. TiC reacts with TiSi2 between 1400–1450°C to form Ti3SiC2. Above 1400° C, decomposition of Ti3SiC2 into TiC commenced and the rate increased with increased temperature and dwell time. Furthermore, the activation energy for the formation and decomposition of Ti3SiC2 was determined.